2022
DOI: 10.1063/5.0076123
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the cholesteric pitch of apolar cellulose nanocrystal suspensions using a chiral hard-bundle model

Abstract: Cellulose nanocrystals (CNCs) are naturally sourced elongated nanocolloids that form cholesteric phases in water and apolar solvents. It is well accepted that CNCs are made of bundles of crystalline microfibrils clustered side-by-side, and there is growing evidence that each individual microfibril is twisted. Yet, the origin of the chiral interactions between CNCs remains unclear. In this work, CNCs are described with a simple model of chiral hard splinters, enabling the prediction of the pitch using density f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 86 publications
(125 reference statements)
4
26
0
2
Order By: Relevance
“…[15,16] While the origin of a chiral mesophase in ChNCs suspensions is not well understood, recent studies on cellulose nanocrystals, a similar colloidal system, have demonstrated that the presence of crystallite bundles determines the chiral nematic pitch. [20,21] Qualitative observation of TEM images confirmed the presence of crystallite bundles (Figure S5, Supporting Information), but further quantitative analysis is required to confirm whether these bundles are also the origin of mesophase chirality in ChNC suspensions.…”
Section: Self-assembly Of Chncs Into Helicoidal Filmsmentioning
confidence: 88%
“…[15,16] While the origin of a chiral mesophase in ChNCs suspensions is not well understood, recent studies on cellulose nanocrystals, a similar colloidal system, have demonstrated that the presence of crystallite bundles determines the chiral nematic pitch. [20,21] Qualitative observation of TEM images confirmed the presence of crystallite bundles (Figure S5, Supporting Information), but further quantitative analysis is required to confirm whether these bundles are also the origin of mesophase chirality in ChNC suspensions.…”
Section: Self-assembly Of Chncs Into Helicoidal Filmsmentioning
confidence: 88%
“…It is known that because CNCs are themselves parallelepiped structures, with twists of their own, that they pack in a chiral structure to maintain efficiency. 112 Recently, hard-particle models of CNCs self-assembling in aqueous and apolar suspensions have been reported, showing an entropic effect of assembly, although the role of water in this was not explicitly described. 112 It would be interesting to see if there is an entropic gain from a displacement of water molecules between two adjoining CNCs in a modeling situation, but this would require explicit water molecules to be simulated.…”
Section: Chiral Nematic Liquid Crystalline States Of Cellulosementioning
confidence: 99%
“…Bundles of naturally sourced cellulose crystallites have been recently proposed to be a key element in the transfer of chirality across different hierarchical levels. 28,33 Our model system offers a well-defined approach to validate this hypothesis and could be extended to other biopolymers, such as chitin, a polysaccharide composed of β-1,4-linked Nacetyl glucosamine. In contrast to cellulose, the chiral nature of chitin nanocrystals (ChNCs) remains elusive 32 even though the in vitro formation of chiral nematic phases 48…”
Section: ■ Conclusionmentioning
confidence: 98%
“…Due to their chirality, CNCs have found applications as nanosized chiral inducers for liquid crystal assemblies and heterogeneous enantioselective palladium catalysis or as chiral templates. , In vitro , when a suspension of CNCs transitions from a diluted to a concentrated regime, spontaneous self-organization results in the formation of a chiral nematic liquid crystalline phase. Although the intrinsic twisted morphology of single CNCs is considered to govern the chirality of these chiral nematic phases, the mechanism by which nanoscale chirality is transferred to a larger scale is debated. While single particles ( i.e. , CNCs) are right-handed, upon self-assembly, an inversion of chirality occurs, resulting in a left-handed chiral nematic phase .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation